Nuovi dati anatomici sulle ghiandole colleteriche dei Pleurosticti (Scarabaeoidea: Melolonthidae, Rutelidae, Dynastidae, Cetoniidae) (Bollettino di zoologia agraria e bachicoltura, 2009)
Further anatomical data on the colleterial glands of Pleurosticti (Scarabaeoidea: Melolonthidae, Rutelidae, Dynastidae, Cetoniidae) Colleterial glands were found in all examined Pleurosticti (14 species) and can be regarded as general feature in this section. Out of 14 species examined, 4 anatomical types of glands were detected throughout: (I) lenticular with single lobe in Cetoniidae (4 spp.);  (II) merely sacklike inmostMelolonthidae (6 spp.); (III) sacklike with one diverticulum in Haplidia etrusca (Melolonthidae); (IV) deeply bilobed in all Dynastidae (3 spp.). In most species, glands are evidently adapted to prevent the entire emptying of their reservoirs; seemingly, they are engaged in harbouring a colony of symbiotic microorganisms, as colleterial glands of other Coleoptera do. Paper is dedicated to the memory of the clever entomologist Vincenzo Lupo (1908-1999).
Keywords: section feature×interspecific variation×supposed endosymbiosis×; section feature; interspecific variation; supposed endosymbiosis